The Impact of Macroeconomic Factors on Foreign Direct Investment in Indonesia from 2007 To 2022: A Vector Error Correction Model (VECM) Approach - Hafidz Zainul Mustofa; Moh. Faizin (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2023)
This study will examine the impact of macroeconomic factors on FDI. The gap in this study lies in the significant changes in economic conditions and investment policies in Indonesia since 2007, which previous studies have not fully explained. The possibility of new factors affecting FDI flows requires more sophisticated analyses. In addition, the relevance of internalized investment theory in the current context of economic globalization has not been widely explored in FDI research in Indonesia. This study uses Secondary time series data and quantitative research techniques. Quarterly data from 2007 to 2022 is the data set used. The research employs the Vector Error Correction Model data analysis technique, with a significance level of 5%. The findings indicate that the exchange rate has an insignificantly negative short-term impact on FDI and a significant negative long-term impact. Then, inflation has a short-term positive and insignificant impact on FDI but a significant negative in the long term. Meanwhile, the interest rate has a significant positive effect on FDI in the long term, but in the short term, it has a negative and insignificant effect.